2017
DOI: 10.1093/nar/gkx567
|View full text |Cite
|
Sign up to set email alerts
|

Control of serine integrase recombination directionality by fusion with the directionality factor

Abstract: Bacteriophage serine integrases are extensively used in biotechnology and synthetic biology for assembly and rearrangement of DNA sequences. Serine integrases promote recombination between two different DNA sites, attP and attB, to form recombinant attL and attR sites. The ‘reverse’ reaction requires another phage-encoded protein called the recombination directionality factor (RDF) in addition to integrase; RDF activates attL × attR recombination and inhibits attP × attB recombination. We show here that serine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 38 publications
(63 reference statements)
1
61
0
Order By: Relevance
“…Nevertheless, 30% of the regenerated plants showed complete commutation into RL YFP:LUC RM and constitutive expression YFP, demonstrating that the switch is able to record the SET event keeping its memory. This also indicates that the SET operation can be fully completed in plant systems as it is in bacteria (43). Presumably, such change at the DNA level of somatic T0 cells should be transmitted to the progeny as other authors reported in Arabidopsis thaliana for Bxb1 (44) and PhiC31 (45).…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, 30% of the regenerated plants showed complete commutation into RL YFP:LUC RM and constitutive expression YFP, demonstrating that the switch is able to record the SET event keeping its memory. This also indicates that the SET operation can be fully completed in plant systems as it is in bacteria (43). Presumably, such change at the DNA level of somatic T0 cells should be transmitted to the progeny as other authors reported in Arabidopsis thaliana for Bxb1 (44) and PhiC31 (45).…”
Section: Discussionsupporting
confidence: 53%
“…To assay in vivo recombination activity of our split-intein ϕC31 integrase, we used a wellcharacterized colour-based galk assay [30][31][32][33] . The attP and attB recombination sites (Supporting Information, Table S1) on the substrate plasmid pϕC31-delPB are in a direct repeat orientation, so that recombination between them causes deletion of the galK gene.…”
Section: Intein-mediated Reconstitution Of Functional ϕC31 Integrasementioning
confidence: 99%
“…Pale-coloured (galK−) colonies on the indicator plates indicate recombination proficiency, whereas red (galK+) colonies indicate incomplete or zero recombination. The coding sequences for Integrase-E N -I N and I C -Integrase-E C (and also appropriate control proteins; see Figure 3C) were cloned into separate low-level expression vectors 30 , as illustrated in Figure 3B. An E. coli strain containing the test substrate was transformed with these plasmids, and recombination activity was assessed by colony colour and by gel electrophoresis analysis of plasmid DNA recovered from the cells ( Figure 3C).…”
Section: Intein-mediated Reconstitution Of Functional ϕC31 Integrasementioning
confidence: 99%
“…Our method only differs in the excision step by the use of a serine integrase. Though it was recently reported that attL and attR of the PhiC31 integrase without its RDF recombine very weakly in E. coli(Olorunniji et al, 2017), our flanking sites only result in attL sites which do not recombine when the integrase is expressed. Next the vector containing the PhiC31 integrase (pInt1) is introduced into the E. coli strain (2).…”
mentioning
confidence: 72%
“…This is in contrast to FRT or loxP scars, negating the risk of chromosomal instability due to unwanted deletions or inversions in the genome. Though it was recently reported that attL and attR of the PhiC31 integrase without its RDF recombine very weakly in E. coli(Olorunniji et al, 2017), our flanking sites only result in attL sites which do not recombine when the integrase is expressed.…”
mentioning
confidence: 72%